Total control. Season 2 [videorecording (DVD)] - Griffiths, Rachel, 1968-; Dale, Darren; Dear, Miranda; Page, Stuart (Screenwriter) (Sundance Now, 2022)
"Alex [Irving] is determined to avoid the pitfalls of the Canberra bubble. She broke her word to her community, but she's not going to be put in that position again. By running for election as an independent, she has a second chance to do it right. Alex will be econfronted by vile online trolls, threats to her family and political opponents riled by the audactiy of a Black woman using her voice. Ultimately, will Alex's determination and the tenacity of her grass-roots-driven team by enough?" --Container.